Applied methods of cost-benefit analysis in health care - McIntosh, Emma (Handbooks in health economic evaluation series., 2010)
This book provides the reader with a comprehensive set of instructions and examples of how to perform a cost-benefit analysis (CBA) of a health intervention. Developed out of a course run by Jordan Louviere at the University of Technology, Sydney, entitled An Introduction to Stated Preference Discrete Choice Modelling it has a particular focus on the use of stated preference survey methods to identify consumer preference data, as well as the use of recent developments incost-effectiveness analysis within a CBA framework. In doing so, the most up to date methodologies for CBA are compiled in a.